Hardware-In-the-Loop Simulation for Semi-Active Suspension System with Using Adaptive Backstepping Approach - Kararsiz, Gokhan; Paksoy, Mahmut; Metin, Muzaffer; Basturk, Halil Ibrahim (IEEE, 2018)
This study presents an approach for designing an adaptive backstepping controller with unmeasured road disturbance to suppress the acceleration level of the vehicle body. It is considered that the unmeasured disturbance consist of a summation of a final number of sinusoidal signals with unknown parameters. Then, the observer is constructed. To generate the actuator force of MR damper, backstepping approach with using adaptive control technique is employed. To show the performance of the proposed controller, a Hardware In-Loop Simulation is prepared.
Keywords: DISTURBANCES; CONTROLLER; Automation & Control Systems; Computer Science; Engineering